Methylene chloride fraction of the leaves of Thuja orientalis inhibits in vitro inflammatory biomarkers by blocking NF-kappa B and p38 MAPK signaling and protects mice from lethal endotoxemia - Kim, Jin-Young; Kim, Hyun Jung; Kim, Sung-Moo; Park, Kyung-Ran; Jang, Hyeung-Jin; Lee, Eun Ha; Jung, Sang Hoon; Ahn, Kwang Seok (ELSEVIER IRELAND LTD, 2011)
Aim of the study: Thuja orientalis (TO) has been a recognized herbal medicine across Northeast Asian countries for thousands of years and used for the treatment of various inflammatory diseases through as yet undefined mechanisms. In this study, we set out to determine whether the anti-inflammatory effects of this plant are mediated to suppress mitogen-activated protein kinases (MAPKs) and nuclear factor-kappa B (NF-kappa B) activation in lipopolysaccharide (LPS)-stimulated RAW 264.7 cells. Materials and methods: RAW 264.7 cells were pretreated with the methylene chloride fraction of TO (MTO) and stimulated with LPS. Nitric oxide (NO) release was determined by the accumulation of nitrite in the culture supernatants and tumor necrosis factor-alpha (TNF-alpha) and IL-6 secretion were determined by immunoenzymatic assay. Inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) expression were evaluated via RT-PCR and Western blotting. NF-kappa B activation was also evaluated by reporter gene assay and electrophoretic mobility shift assay (EMSA). In addition, the protective effect of MTO was evaluated by use of the LPS-induced endotoxin shock model in mice. Results: We found that MTO significantly suppressed LPS-stimulated NO and IL-6 production without affecting cell viability. MTO inhibited the expression of LPS-induced iNOS and COX-2 protein and their mRNA expression. Also, TNF-alpha and IL-6 secretion were decreased by MTO in both PMA and ionomycin-stimulated splenocytes. As a result, MTO inhibited pro-inflammatory cytokines such as TNF-alpha and IL-6, which is hypothesized as being due to the suppression of LPS-induced p38 MAPK and NF-kappa B activation. Moreover, MTO improved the survival rate during lethal endotoxemia by inhibiting the production of TNF-alpha in an animal model and our LC-MS analysis showed that a major component of MTO was pinusolide. Conclusions: We demonstrate here the evidence that the methylene chloride fraction of Thuja orientalis (MTO) potentially inhibits the biomarkers related to inflammation in vitro and in vivo, and might be provided as a potential candidate for the treatment of inflammatory diseases. (C) 2010 Elsevier Ireland Ltd. All rights reserved.
Keywords: NITRIC-OXIDE SYNTHASE; TUMOR-NECROSIS-FACTOR; TRANSCRIPTION FACTOR; BIOTA-ORIENTALIS; GENE-EXPRESSION; DOWN-REGULATION; TNF-ALPHA; CELLS; ACTIVATION; SHOCK